Kainate/AMPA receptor antagonists are anticonvulsant against the tonic hindlimb component of pentylenetetrazol-induced seizures in developing rats - Velísek, L; Kubová, H; Mares, P; Vachová, D (Pharmacology, biochemistry, and behavior, 1995)
Non-NMDA receptor antagonists CNQX, DNQX, and NBQX (10-40 mg/kg IP) were tested against pentylenetetrazol-induced (100 mg/kg SC) seizures in 7 to 90-day-old rats. All three drugs significantly decreased the incidence of tonic hindlimb component of tonic-clonic pentylenetetrazol seizures, often in favor of increased incidence of forelimb tonus throughout development. In addition, in 7 to 25-day-old rats, DNQX and NBQX decreased the severity of seizures due to a decrease in total incidence of the tonic component of tonic-clonic seizures compared to age-matched controls. However, neither drug was able to consistently suppress the incidence or increase latency to onset of clonic and tonic-clonic pentylenetetrazol seizures. The data suggest that, during development, non-NMDA receptor transmission may play a role in the generation of the tonic component, but not in the generation of other components of pentylenetetrazol-induced seizures.
Keywords: Muscle Tonus; nervový přenos; stárnutí; Receptors, Kainic Acid; krysa rodu Rattus; Synaptic Transmission; Epilepsy, Tonic-Clonic; záchvaty; antikonvulziva; chování zvířat; potkani Wistar; receptory kyseliny kainové; 6-kyano-7-nitrochinoxalin-2,3-dion; Rats, Wistar; svalový tonus; Quinoxalines; mužské pohlaví; zvířata; Anticonvulsants; epilepsie tonicko-klonická; 6-Cyano-7-nitroquinoxaline-2,3-dione; Aging; zadní končetina; Pentylenetetrazole; Rats; Animals; pentylentetrazol; Behavior, Animal; Male; Hindlimb; Seizures; AMPA receptory; chinoxaliny; Receptors, AMPA